Production of an aged cheese from carabao's milk using a local probiotic starter - Puentespina, Ingrid P.
Cheesemaking has been used as a milk preservation technique for centuries. With the utilization of a probiotic lactic acid bacteria strain, cheese can not only prolong the shelf life of carabao’s milk but also act as a vehicle for the consumption of these beneficial gut health microorganisms. This study aimed to produce an aged cheese from carabao’s milk using a locally produced probiotic cheese starter. The physicochemical (moisture content, water activity, pH, and titratable acidity) and microbiological (total mesophilic, yeast and mold, and lactic acid bacteria counts) characteristics were monitored throughout a 12-week ageing period. The final product was evaluated using a consumer acceptability test. It was found that the low moisture content of the prototype affected its physicochemical, microbiological, and sensory characteristics greatly. The probiotic starter culture was also found to have survived the production and ageing processes to the extent of possibly retaining its probiotic effects. The prototype was found to be acceptable by the general public. However, improvements to the formulation were recommended through the screening of other potential starter cultures as well as the regulation of humidity of the ageing environment to better control ripening.